A high torque density outer-rotor permanent magnet motor for in-wheel electric vehicle applications - Lu, Jiping (Nanyang Technological University, 2022)
Nowadays, environmental problems including carbon emission attract much concerns around the globe. Transition from conventional Internal Combustion Engine vehicle to Electric Vehicle (EV) is one of the useful solutions to relieve the threats to the environment, which will also promote the use of electric machines for EVs. In-wheel motor is a promising candidate for EV due to its advantages like compact structure. However, because of the space constraint in wheeling applications, it is desirable to utilize the limited space to the great extent to maximize its value. This project aims to discover useful strategies to enhance the torque density of existing outer-rotor permanent magnet (ORPM) motors used in in-wheel EVs while simultaneously behave well in other critical aspects, including torque ripple and permanent magnet (PM) consumption rate, so as to obtain a more desirable solution. Conventional solutions involve 3-phase, 30-slot, 32-pole surface-mounted PM ORPM synchronous motors with single- or double-layer fractional-slot concentrated winding and 3-phase split-pole ORPM vernier motors with surface-mounted or spoke-type PM. Improvements on PM topologies and winding configurations was proposed based on the original ORPM vernier motor models to reach the aforementioned targets. Simulation and optimization reveal that one of the proposed models with reduced-length radial and circumferential PMs in outer-rotor can reach very high torque density compared with other models while at the same time attaining desirable torque ripple and PM utilization ratio. However, it also has other flaws such as poor voltage quality that constrain its applications and thereby under enhancement.